Coupled modelling of the Minho and Lima estuaries: biochemical response to extreme events and interaction of plumes estuarine - Oliveira, Vítor Hugo Pessoa (2021)
In the last years, due to human activity, increase in the number of inhabitants in the coastal areas and climate change, estuaries have undergone major changes, both in dynamics and in water quality. The Minho and Lima estuaries are separated only by 20 km, have great ecological value and are under the dependence of dams that control the freshwater input. In this context, arises the need and interest to study the dynamics and interaction between the Minho and Lima estuarine plumes, as well as the impact of extreme river discharges events on the nutrient dynamics in both estuaries, as well as the response time of the Minho estuary to a point discharge of pollutants by a tributary (river Coura). To carry out these studies, a numerical application including simultaneously the two estuaries mentioned was developed. This includes the hydrodynamic and water quality module of the Delft3D numerical model, which were calibrated through a large set of simulations and using a vast set of data monitored in situ. Subsequently, several scenarios were defined and simulated in order to achieve the objectives of this work, and the respective results were analysed in a comparative way. To study the intrusion and dynamics of the estuarine plumes, the trajectories of passive tracers emitted in each estuary were simulated. In order to study the impact of extreme river discharge events on nutrient dynamics, three numerical simulations were carried out, characterized by the variation of the river flows to the estuaries (1st simulation: baseline; 2nd simulation: flood scenario, with double fluvial discharges comparing to the baseline; 3rd simulation: discharge of ecological flows (dry season). To study the response time of the Minho estuary to a punctual discharge of pollutants, two additional simulations were carried out, considering a discharge in neap tide (10/08/2012) and in spring tide (19/08/2012). From the analysis of the results it was verified: 1) there is interaction between estuaries under study, both during the summer and the winter seasons; 2) the movement of estuarine plumes depends on the direction and intensity of the wind and the intensity of the river discharge (in the summer season both plumes tend to move southward in response to the predominant north wind, while in winter the opposite is observed); 3) during periods of higher river discharge there will be no major impact on estuarine biota, both in summer and winter, because there will be higher concentrations of nutrients and the variation in the concentrations of dissolved oxygen is insignificant; 4) the discharge of ecological flows by dams will have a major impact on the estuarine biota, mainly in the Lima estuary, since the estuary suffers an average decrease of 2 mg O2/ L (more anoxic estuary, which may result in the death or migration of biological species); and (5) in neap tide, the estuary has a longer response time than in a spring tide. In summary, the model developed in this work contributed to: 1) increase the knowledge about the interaction and dynamics of the plumes; 2) perceive the direct impact that dams may have on estuaries under study (since river discharges are controlled by them); and 3) understand the response time it takes for the Minho estuary to react to a point discharge.